Creating Favorable Macroeconomic Environment for Manufacturing Industry in Kenya - Murunga, James; Mugambi, Purity (Machakos University, 2019)
Kenya’s vision 2030 which is a development blue print seeks to transform Kenya into a newly industrialized middle-income country that offers high quality life to all its citizens. To achieve its goal, it recognizes the role of manufacturing sector in creation of employment and wealth as well as its vital contribution to the economy’s GDP. The big four agenda launched by the president of the republic of Kenya in 2017 identified manufacturing as a key pillar to propel Kenyan economy and aims to raise the sector’s contributions to the GDP from 9 percent to 15 percent by 2022. The agenda seeks to concentrate on improving specific sectors in the manufacturing industry; textile and apparel, food and beverages, leather, timber, cement, automotive, chemicals, and pharmaceutical. Creating a favorable macroeconomic environment is a key enabler to achieve the manufacturing sector goals. According to Dunning, J.H. (2004), among the macroeconomic factors that affect manufacturing are economic development and growth, level of inflation, exchange rate, interest rate and foreign direct investment. This paper seeks to look deeper into macro-economic factors and to analyze their impact on the manufacturing sector. Augmented Dickey Fuller, Phillips Perron and Zivot- Andrews test are used to test for presence of unit root among the variables. The results reveal that variables are integrated of order zero, one and two. In this regard, the study adopts ARDL bounds test. The results reveal that inflation, exchange rate and gross domestic product as the determinants of manufacturing sector in Kenya. The study therefore recommends that Kenyan government should stabilize the flow of foreign exchange through diversifying revenue base of the economy, provision of incentives to encourage the consumption of locally produced goods and ensure that the proceeds of corrupt practices are not domiciled in foreign accounts. The government should achieve prudent management of national financial resources as well as borrowings from abroad, initiate policies to minimize capital flight through repatriation of earnings or outright withdrawal by foreign interests. With regard to negative effect of rise in GDP to manufacturing sector, Kenyan government should pursue policies and programmes aimed at controlling the underground economy. Such policies may include improvement of cross-sectoral cooperation involving customs, national police, Kenya Defence Forces.
Keywords: Manufacturing; GDP.